Superwetting graphene-based materials: From wettability regulation to practical applications. (April 2023) - Chen, C.; Fei, L.; Lu, L.; Li, B.; Raza, S.; Shen, L.; Lin, H.
Abstract: Recent achievements in the construction of graphene-based materials with superwetting properties have been developed and received significant research attention. Deeply understanding and effectively controlling the wettability of graphene-based materials is crucial for its fundamental research and functional application. Therefore, in this review, after a brief introduction to the intrinsic wettability of graphene and graphene oxide (GO). The strategies for manipulating the wettability of graphene-based materials to achieve superwetability are summarized and discussed, including chemical composition regulation and multiscale structure construction. Then, we also propose a framework for the promising applications of graphene-based superwetting materials in oil-water separation, droplet manipulation, self-cleaning coatings and energy-related applications. Finally, we provide our views and recommendations on the challenges and future research directions in this emerging and promising research field. Graphical abstract: Image 1 Highlights: The research progress of superwetting graphene-based materials has been reviewed. The intrinsic wettability of graphene and graphene derivatives is discussed. The wettability regulation strategies of graphene-based materials are summarized. The promising applications of graphene-based superwetting materials are introduced. Future perspectives for superwetting graphene-based materials are given.